Identification of a conserved virion-stabilizing network inside the interprotomer pocket of enteroviruses - Justin W. Flatt (Nature Portfolio, 2021)
Flatt, Butcher and colleagues use cryo-EM to report on coxsackieviruses B3 and B4 bound to different capsid binders. Comparative analysis revealed the residues that form a conserved virion stabilizing network at the interprotomer site, and showed the small molecule properties that allow anchoring in the pocket to inhibit virus disassembly.